Crafting behaviors a quantitative study of consumer behavior on artisanal/craft ice cream - Falco, Jacint Dave; Ong, Josef Matthew T.; Patosa, Reil Jan S. (2022.)
Artisanal craft. The term refer to an activity that involves skillfully creating something through traditional means or by using one's hands. The researchers focused on Artisanal ice cream products and how consumers behave towards them. This study aims to identify the consumer's preferences and buying behavior on artisanal ice cream products whilst considering various external factors such as demographics, attitude, beliefs, and habits. The researchers used a descriptive quantitative research design to gather descriptive yet quantitative information for the statistical analysis of the target population sample. The chosen respondents in this study were artisanal ice cream consumers within Iloilo City and the province of Capiz. Considering gender, data analysis has identified a significant difference between this factor and the price of an artisanal product, with females considering relevant price-led decisions. Age group was also associated with Brand Relevance, with Gen Z and Gen x age groups being significantly more concerned than Baby Boomers regarding the brands of the products they purchase. Further analysis even exhibited an association between Brand Relevance and Educational Attainment, with Postgraduate Degree attainers being more concerned with the brands of products they purchase than College attainers. Moreover, the Exclusivity factor was identified to be significantly associated with Brand Relevance, Price, and Color and quality, Chi-Square Test also revealed that there was a significant difference between Age Group and Color and Quality. From these results, it was concluded that there were prominent factors influencing consumer behavior, consumer demographics can be compared and contrasted to such factors, and there were differences between the factors affecting consumer behavior on artisanal ice cream.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, June 2022.